"Varför blev det så här?" : om utemiljön på Herrgården från 60-talet och framåt - Smekal, Hanna (SLU/Landscape Architecture (until 121231), 2011)
The residential yard at Kvarteret Landsfiskalen 1, in the area Herrgården in Rosengård, Malmö was built in 1971 and has since then been reconstructed twice, in 1984 and 2008. The yard is found in an area which was built during the years 1965 – 1974, a period in which the swedish goverment approved a decision to build one million homes, and much of the events in this particular yard is also typical for the process in many other areas built during the same period. At the original construction the design of the yard was entirely incused by the pressure in time and finance, one was under at that time, in order to over- come the housing shortage. The design it has nevertheless been given, reflects the esthetic ideals of that time well. The building of the area was barely finished when the swedish authori- ties started handing out grants in order to support the rearmament of the outdoor environment in the areas built during the so called ”million program”. This grant was available until 1986 and altogether 1700 projects were conducted. The yard at Kvarteret Landsfiskalen was also reconstructed during this time, although it is somewhat unclear whether this was part of the public grants since the yard was privately owned at this time. But what stands clear is that also the rearmament was quite typical for its time. The design of the yard was carried out alongside the residents of that time, and a variety of vegetation was added, along with a great many other supplements, such as a more cohesive playarea and patios for the residents at the ground floor. During the next twenty years, the large population in the area together with some vandalism contributed to an extensive wearing of the outdoor environment, and when the buildings aroung the Kvarteret Landsfiskalen 1 and 2 where bought by the municipal housing corporation, MKB in 2006 it became clear that the carrying through of yet another reconstruction of the yard was necessary. This time the danish firm Gehl architects were consulted, and they pre- sented a strategy program for the whole neighboorhood of Herrgården, which later resulted in a design created by the swedish company Grontmij AB, which was constructed during 2008. This design differs remarkably from the former one, such as from the immediate surroundings, and is a clear signal that a new beginning is wanted through the new design. The residents have also been a part of the process this time, and a careful note of overcoming past problems through the new design has been taken.